“To Which Homelands of Silence”. Nonortodox Patriotism of Juan José Saer (Castilla. Estudios de Literatura, 2019)
Juan José Saer´s first novels and short stories were initially classified, in the beginnig of 1960s, as tipical for the so called regional fiction, distant to Buenos Aires cultural athmosphere. (along with Héctor Tizón, Haroldo Conti or Daniel Moyano´s work). This article shows, nevertheless, how Saer´s fiction transforms emotional allegiance to the homeland into an attitude which goes far beyond the traditional patriotism. His protagonists transfer their early experience of perceiving local geography to the whole univers. To prove this, the article refers to historical and philosophical explanations of patriotism, as well as to literary and cultural criticism focused on the question of space and emigration.
Keywords: Juan José Saer; 20th-21st Century Spanish American Fiction; Patriotism; Emigration